Epidemiology, Endovascular Treatment, and Prognosis of Cerebral Venous Thrombosis: US Center Study of 152 Patients. Issue 6 (June 2017) - Salottolo, Kristin; Wagner, Jeffrey; Frei, Donald F.; Loy, David; Bellon, Richard J.; McCarthy, Kathryn; Jensen, Judd; Fanale, Christopher; Bar‐Or, David
Abstract : Background: Cerebral venous thrombosis is a rare cause of stroke that poses diagnostic, therapeutic, and prognostic challenges. Mainstay treatment is systemic anticoagulation, but endovascular treatment is increasingly advocated. Our objectives were to describe the epidemiology, treatment, and prognosis of 152 patients with cerebral venous thrombosis. Methods and Results: This was a retrospective study of consecutive cerebral venous thrombosis cases from 2006 to 2013 at a comprehensive stroke center through hospital discharge. Predictors of full recovery (modified Rankin Scale scores 0–1) were analyzed with multiple logistic regression and presented as adjusted odds ratios (AORs) with 95% confidence intervals (CIs). The population was young (average age: 42 years), majority female (69%), and commonly presenting with cerebral edema (63%), and 72% were transferred in. All patients received systemic anticoagulation; 49% (n=73) required endovascular treatment. Reasons for requiring endovascular treatment included cerebral edema, herniation, or hemorrhagic infarct (n=38); neurologic decline (n=17); rethrombosis, persistent occlusion, or clot propagation (n=10); extensive clot burden (n=7); and persistent headache despite anticoagulation (n=1). There were 7 (10%) procedural complications. Recanalization was successful (61%), partial (30%), and unsuccessful (9%). Overall, 60% fully recovered. Positive predictors of full recovery included hormonal etiology, particularly for patients who were transferred in (AOR: 7.06 [95% CI, 2.27–21.96], interaction P =0.03) and who had migraine history (AOR: 4.87 [95% CI, 1.01–23.50], P =0.05), whereas negative predictors of full recovery were cerebral edema (AOR: 0.11 [95% CI, 0.04–0.34], P <0.001) and motor weakness (AOR: 0.28 [95% CI, 0.09–0.96], P =0.04). Conclusions: As one of the largest cohort studies, our findings suggest that cerebral edema, history of migraine, and hormonal etiology were prognostic and that endovascular treatment might be a safe and effective treatment for cerebral venous thrombosis when conventional management is inadequate.